Ewing's Sarcoma of the Mandible: A Rare Case Report and Review of Literature - Sanki Reddy Shailaja; Marthala Manjula; Manika; Chappidi Vani; Ainampudi Bhargavi Krishna; Gannepalli Asha Lata (Wolters Kluwer Medknow Publications, 2011)
Ewing's sarcoma is a small, round and blue cell malignancy that most commonly arises in the skeleton of adolescents and young adults. Although it may appear in any bone, it is more common in the axial skeleton, rarely involving the jaws (1-2% incidence mostly in the mandible). In this article, we are reporting a rare case of Ewing's sarcoma of mandible in an 18-year-old female patient with the typical radiographic appearance of spiculated bone formation